Technology management in digital library information services (Research, Society and Development, 2022)
The management of information services in a digital library has in its differential the elimination of physical and temporal barriers, thus providing quick access to the desired information. Enabled by the use of information and communication technologies and combined with the information skills and competences of librarians, themes that were addressed here, enable actions that aim to meet the informational needs of users. Based on this premise, in a succinct way, this article is a narrative review, covering books and scientific articles, these published in the Portal de Periódicos da Capes. It aims to briefly discuss the management of information services in a digital library, based on the theoretical framework adopted. To support the proposed approaches, a bibliographic survey of the works that deal with the themes was carried out: digital library, information and communication technologies, information skills and competences of the librarian and management of services in libraries. It is observed that, through the analysis of the different definitions regarding the management of services in digital libraries, in the researched literature the services offered by the digital library are not limited only to the access and use of information, but encompasses all other activities of managerial and administrative nature of the library and its users.